2018
DOI: 10.1590/1413-70542018421005217
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction during harvest operations in five tropical soils with different textures under eucalyptus forests

Abstract: Traffic of farm machinery during harvest and logging operations has been identified as the main source of soil structure degradation in forestry activity. Soil susceptibility to compaction and the amount of compaction caused by each forest harvest operation differs according to a number of factors (such as soil strength, soil texture, kind of equipment, traffic intensity, among many others), what requires the adequate assessment of soil compaction under different traffic conditions. The objectives of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…soil water content at the time of harvesting [9,11,13,30], soil texture [23,32], initial soil bulk density, relative bulk density [21], organic matter content, and duff thickness [31] can all play an important role in how a soil will physically respond to ground-based machine traffic (Table 1). In the context of this article, slope is referred to as the longitudinal incline or decline of the terrain located on machine operating trails.…”
Section: Terrain-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…soil water content at the time of harvesting [9,11,13,30], soil texture [23,32], initial soil bulk density, relative bulk density [21], organic matter content, and duff thickness [31] can all play an important role in how a soil will physically respond to ground-based machine traffic (Table 1). In the context of this article, slope is referred to as the longitudinal incline or decline of the terrain located on machine operating trails.…”
Section: Terrain-related Factorsmentioning
confidence: 99%
“…Several studies focused on the effects of texture on soil compactibility [32,39]. Naghdi et al [23] concluded that soil bulk density and rut depth showed greater increases in clay loam soil than in a sandy loam soil during groundbased skidding.…”
Section: Soil Texture and Other Factorsmentioning
confidence: 99%
“…Martins et al. () also observed that for the highest traffic intensities, the occurrence of compacted samples was widespread regardless of soil and depth. Keeping traffic to only a few passes may not always prevent soil compaction, but less extensive skidding trails may also be operationally more cost‐effective (Gilanipoor, Najafi, & Heshmat Alvaezin, ).…”
Section: Resultsmentioning
confidence: 91%
“…We also employed a different technique for analysing soil compaction data with the aid of correspondence analysis, which may help to settle a decade‐old problem for statistically analysing the number, or proportion, of compacted samples after a given intervention (e.g. Dias Junior et al., , ; Martins, Dias Junior, Ajayi, Takahashi, & Tassinari, ).…”
Section: Introductionmentioning
confidence: 99%
“…O manejo incorreto do solo produz efeitos como compactação superficial e redução da produtividade agrícola (MOLINA JR., 2017). As máquinas e os implementos agrícolas são os principais responsáveis pela compactação do solo nas áreas agrícolas (MARTINS et al 2018).…”
Section: Introductionunclassified